استخدام ادوات التحليل المكاني في تقنية نظم المعلومات الجغرافية في نمذجة وتحليل خصائص المياه الجوفية في قضاء الشطرة وتقييم صلاحيتها للاستخدامات المختلفة - سوادي نجيبان أ.م.د. حسن; حمود حاشوش م.م. وسام (Journal of College of Education, 2021)
The research study of the chemical and physical characteristics of the groundwater in the district of Shatra / center of Dhi Qar province in southern Iraq and modeling tools of spatial analysis of geographic information systems (GIS), the study was based on analysis of the concentrations of ions in the positive and negative values of electrical conductivity and the concentration of total dissolved salts, pH and total brackish the proportion of sodium absorption .autam take advantage of the spatial analysis tools in GIS in building a database hydrochemical the region and modeling and produce statistical surfaces which are designed against which the spatial distribution maps of these characteristics has been shown through research that the algorithm weight distance inverted (IDW) is the best appropriate ways for the production of the spatial distribution of the characteristics of groundwater maps in the study area, and has been producing the map quality and validity of the groundwater in the study area for agricultural uses, also built the water unfit to drink human and industries of various exception of building and construction and fit to irrigate crops, but resistance to salinity them after comparing international specifications .